Bio-stimulatory effects of bull urine (BU), PRID and GnRH on estrus induction and ovarian activity in pubertal anestrus Sahiwal heifers - AHMED, ABRAR; TIWARI, R P; MISHRA, G K (The Indian Journal of Animal Sciences, 2016)
The present study was designed to assess the bio-stimulatory effect of bull urine (BU) exposure, administration of progesterone impregnated intravaginal device (PRID) in combination with PGF2a and gonadotropin releasing hormone (GnRH), (PRID-PG-GnRH) and GnRH in combination with PGF2a (GnRH-PG-GnRH) on induction of estrus and resumption of ovarian activity in pubertal anestrus Sahiwal heifers. Thirty two pubertal anestrus Sahiwal heifers were randomly divided in to 4 groups viz., Gr.1, (n=8, BU), Gr.2, (n=8, PRID-PG-GnRH), Gr.3, (n=8, GnRH-PG-GnRH) and Gr. 4, (n=8, Control). Significantly lesser proportion of anestrus Sahiwal heifers were induced to estrus (25%) following BU exposure than PRID-PG-GnRH (100%) and GnRH-PG-GnRH (87.50%) treated heifers. However, there were no heifers induced to estrus in control group during the experiment. The time interval taken for onset of estrus (days) was shorter in PRID-PG-GnRH (8.00±1.51) and GnRH-PG-GnRH (8.00±1.25) than BU exposed heifers (23.00±2.41). On ultrasonographic imaging, no definite growth patterns of ovarian follicles were observed in BU exposed and control groups. However, definite growth pattern of ovarian follicles were recorded in PRID-PG-GnRH and GnRH-PG-GnRH treated heifers. Significant decrease in the number of small follicles from day 3 to 7 in PRID (14 vs 5) and in GnRH (13 vs 4) treated heifers. However, increase in the number of large follicles were observed in heifers treated with PRID-PG-GnRH (0 vs 1.87) and GnRH-PG-GnRH (0 vs 2) from day 0 to 7, respectively, as compared to control group. The overall conception rate in BU exposed heifer was lower (25%) than PRID (50%) and GnRH (50%) treated heifers. Bull urine (BU) mediated induction of estrus is significantly lower in pubertal anestrus Sahiwal heifers than PRID+PG and GnRH+PG treated heifers.